2020
DOI: 10.1002/jso.26210
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal carcinomatosis in gastric cancer: Are Hispanics at higher risk?

Abstract: Background: A recent study from our group identified Hispanic race/ethnicity as an independent predictor of peritoneal carcinomatosis (PC) in gastric cancer. We sought to identify the tumor factors that might contribute to this strong association in Hispanics. Methods: California Cancer Registry data were used to identify patients diagnosed with gastric adenocarcinoma from 2004 to 2014. Logistic regression analyses were performed to determine odds ratios for cancer stage, tumor location, grade, histology, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…After title and abstract screening, 38 studies were considered potentially eligible. After full text screening, seventeen studies were included [ 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The study flowchart and reasons for exclusion are shown in Figure 1 and Appendix B .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After title and abstract screening, 38 studies were considered potentially eligible. After full text screening, seventeen studies were included [ 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The study flowchart and reasons for exclusion are shown in Figure 1 and Appendix B .…”
Section: Resultsmentioning
confidence: 99%
“…The study flowchart and reasons for exclusion are shown in Figure 1 and Appendix B . In sixteen studies, information on incidence numbers of synchronous gastric peritoneal metastases was provided [ 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Risk factors for gastric peritoneal metastases were reported in four studies [ 15 , 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are vast documented disparities in clinical and patient‐reported outcomes across most malignancies, with overwhelming evidence suggesting that HLs are at a critical disadvantage. Hispanics and Latinos, specifically, present with more advanced disease and have a poorer prognosis for several different cancers relative to NHWs [10–16].…”
Section: Social Determinants Of Health In Hispanic and Latinos: Effects On Cancer Outcomesmentioning
confidence: 99%